ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INITIAL RETURN PADA PERUSAHAAN NON KEUANGAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) DI BEI PERIODE 2010-2015 - Nuryasinta, Amalia; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2017)
Most of company will do a variety of ways to meet the capital needs in order to expand and maintain its business. The company may issuing new shares and sell it to the public, it’s called Initial Public Offering (IPO). This research aims to analyze the influence of Return On Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Size and Proceed to Initial Return (IR) non-financial companies in Indonesia Stock Exchange during 2010-2015. The number of sample used in this research were 113 non-financial companies doing IPO period of 2010 until the end of 2015. Secondary data were obtain from prospectus when Initial Public Offering. The analytical method used in this research is Multiple Linear Regression Analysis where previously performed classical assumption that includes Normality Test, Multicollinearity Test, Autocorellation Test, and Heteroskedastisitas Test with significance level of 5%. The study found that Size is positively significant influenced to Initial Return (IR). Proceed is negatively significant influenced to Initial Return. On the other hand, Return On Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR) have no significant effect on Initial Return. Based on the coefficient determination, variable Return On Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Size, and Proceed have 28,7% effect against Initial Return. While the remaining 71,3% is influenced by other variables that are not used in this study.